2019
DOI: 10.1017/s1463423619000252
|View full text |Cite
|
Sign up to set email alerts
|

How do physicians and nurses in family practice describe their care for patients with progressive life-limiting illness? A qualitative study of a ‘palliative approach’

Abstract: Aim: To explore how a palliative approach to care is operationalized in primary care, through the description of clinical practices used by primary care clinicians to identify and care for patients with progressive life-limiting illness (PLLI). Background: Increasing numbers of people are living with PLLI but are often not recognized as needing a palliative approach to care. To meet growing needs, generalists such as family physicians will need to adopt a palliative approach to care in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Documentation of advance care planning discussions, clinic and community nursing involvement, addressing psychosocial and spiritual needs and addressing caregiver wellness were care processes that distinguished between patients receiving PAC and not receiving PAC. In previous research, family physicians reported feeling capable of meeting the palliative needs of many patients, [2,35] however they have also reported doing so without a speci c plan or approach. [36] Patients with progressive life-limiting illness have varying needs over the last year of life, beyond medical treatment for physical symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Documentation of advance care planning discussions, clinic and community nursing involvement, addressing psychosocial and spiritual needs and addressing caregiver wellness were care processes that distinguished between patients receiving PAC and not receiving PAC. In previous research, family physicians reported feeling capable of meeting the palliative needs of many patients, [2,35] however they have also reported doing so without a speci c plan or approach. [36] Patients with progressive life-limiting illness have varying needs over the last year of life, beyond medical treatment for physical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence revealing the bene ts of palliative care for patients with chronic, progressive life-limiting illness. [1][2][3][4][5] Fewer people are dying suddenly and most will live for a period of time with high healthcare and other needs. [6] Despite this knowledge, efforts to integrate, describe and evaluate palliative care in and across the healthcare system have not achieved the level of uptake and sustainability required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the gap between conceptual descriptions and competencies, and observable measurable care processes in practice, in our previous work, we qualitatively described a palliative approach to care (PAC) in primary care, from the perspective of primary care physicians and nurses caring for patients with progressive life-limiting illnesses [ 2 ]. In this study, we sought to measure the extent to which PAC is provided in a large, urban inter-professional family health team (FHT) setting in one city in Canada.…”
Section: Introductionmentioning
confidence: 99%